Linguistic Study: Exploring its Philosophical Underpinnings - Dewi, Ning Ratna Sinta (SALEE: Study of Applied Linguistics and English Education, 2022)
Linguistic is an alternate term that is frequently used in the language term. Linguistics is part of philosophy. Philosophy is the main core of all knowledge that human beings learn. Philosophy and language are inseparable units. The term ‘language philosophy’ refers to the study of philosophy concerning language or linguistics. This study discovers the language and linguistic issues under the frame of language philosophy. The qualitative approach is employed by conducting critical literature reviews on various relevant literature. In critical literature reviews, the writer analyzed the linguistic literature from the perspective of language philosophy.